Analysis Hydration Status of National Triathlon Athletes Towards SEA GAMES 2025 - Azhar Jauza Muthmainnah; Boyke Mulyana; Gafur Ammar Santoso (Journal of Physical Education Health and Sport, 2025)
Hydration status plays a pivotal role in maintaining athlete performance, especially in endurance sports such as triathlon, which involve prolonged and intense physical exertion. This study aimed to analyze the hydration status of Indonesian triathlon athletes undergoing national training in preparation for the 2025 SEA Games. Using a quantitative descriptive method with a cross-sectional design, data were collected from 10 purposively selected athletes. Instruments included Omron Karada Scan for anthropometric assessment and urine test strips with color charts to evaluate hydration levels pre- and post-time trial. Results showed that 90% of athletes experienced weight loss averaging 0.8–0.9 kg, indicating fluid loss. Urine analysis revealed that 50% of athletes were mildly dehydrated, 30% adequately hydrated, and 20% well hydrated. One athlete showed increased body weight with a light urine color, suggesting effective fluid intake. These findings highlight the need for tailored hydration strategies and regular monitoring during training to minimize dehydration risks and support optimal performance. Coaches and sports health professionals are advised to incorporate hydration management protocols into daily training regimens for triathletes.